Eco-inovação e governança colaborativa: um estudo no complexo industrial e portuário do Pecém - Menezes, Bárbara Sampaio de (2023)
In this thesis, we seek to understand the relationship between eco-innovation and collaborative governance in the Pecém Industrial and Port Complex. To this end, three articles were developed with the purpose of filling gaps identified in the literature. In the first article, identifying trends on eco-innovation and governance, through an international systematic review, the meta-analysis technique was applied, a systematic verification, through the SCOPUS database, using the keywords “Eco-innovat *” and “Governance”. Furthermore, a co occurrence analysis and hot-topics mapping were carried out using the VosViewer software. 68 publications were analyzed from 2005 to 2023, it was found that there is an increase in publications in areas related to eco-innovation and governance in the last two years. It was noticed that the majority of publications come from the United Kingdom, the author who publishes most in these areas is René Kemp and there was a hot-topic between eco-innovation and governance approaches. It was concluded, therefore, that eco-innovation and governance are terms that still need to be researched together, especially in countries like Brazil. The second article verifies the determinants and barriers to eco-innovation in the Pecém Industrial and Port Complex in the light of collaborative governance. The methodology used was qualitative, exploratory-descriptive, through a case study in the Pecém Industrial and Port Complex (CIPP). Members of CIPP's initial collaborative governance were interviewed and content analysis was used with the help of Atlas.Ti and Iramuteq software. As results, it is noted the existence of product, process and organizational eco-innovations at CIPP, as well as an attention focused on eco-innovations at the system level, due to the production of green hydrogen. It is also clear that, in the case of the CIPP territory, the factors that are most determining for this application of eco-innovations are external, as well as variables driven by the market and regulatory factors. As for barriers to eco-innovation, a series of intertwined challenges can be seen, ranging from social and economic concerns to governance aspects, as well as financial obstacles and personnel obstacles. The third article aims to analyze the influence of collaborative governance on eco-innovations in the Pecém Industrial and Port Complex. Members of CIPP's initial collaborative governance were interviewed and content analysis was used with the help of Atlas.Ti and Iramuteq software. As results, it is noted that it is necessary to draw a parallel between two moments of this collaborative governance, with the Pecém Pact (2011 – 2014) and its resumption in 2023. It appears that the initial conditions of this current process were due to of the green hydrogen hub and that there is cooperation between the parties, despite challenges, given the region's complexity. The facilitating leadership is considered the Association of CIPP Companies, however the institutional design of this resumption is not yet fully established, regarding the rules and functions of each governance component. In the collaborative process, it appears that there is commitment, trust, dialogue, but they need more meetings and, despite seeing a common mission, there are still no relevant intermediate results. It is understood that there is an influence of collaborative governance on existing eco-innovations in the region, but it is necessary for them to be seen according to the triple bottom line. Finally, it is concluded that for collaborative governance to be more effective in the region, it is necessary for the institutional design to be more robust, as well as for there to be greater participation from civil society and universities and due monitoring of actions.